Comprehensive investigation on bond mechanism of embedded through-section fiber-reinforced polymer bars to concrete for structural analysis. (May 2020) - Van Hong Bui, Linh; Stitmannaithum, Boonchai; Jongvivatsakul, Pitcha
Abstract: This study investigates the bond behavior between embedded through-section (ETS) fiber-reinforced polymer (FRP) bars and concrete, as well as its effect on the structural performance of beams strengthened in shear with ETS bars, through experiments, analytical evaluations, and numerical simulations. A series of pullout tests was carried out to analyze the bond mechanism between ETS bars and concrete for various influences such as embedment length and ETS stiffness. Together with previous data, a comprehensive analytical method for defining the ETS–concrete interfacial profile is proposed. Additionally, the proposed bond model is used to build a new method of predicting the ETS shear resisting force and assessing the absorption energy of strengthened beams. Results indicate that the developed bond model is reasonable for simulating ETS–concrete interfaces, and the method for deriving the shear contribution of ETS FRP bars through bonding-based mechanism shows good performance compared to other shear models. Bonding parameters such as interfacial ductility index ( B ) and interfacial energy ( G f ) are observed to strongly affect the performance of strengthened members. Moreover, finite element (FE) simulations of beams strengthened with ETS bars were conducted, and the proposed bonding approach was utilized. Comparisons between the results achieved from FE modeling and experiments clarify that FE simulation with the proposed bond model is effective for analyzing shear strengthened beams by ETS bars. Highlights: Bond mechanism between embedded through-section (ETS) fiber-reinforced polymer (FRP) bars and concrete is studied. Bond model representing the interfacial mechanism of ETS FRP bars to concrete is developed. A new approach for deriving shear resisting force of ETS bars based on bonding analysis is proposed. Effects of interfacial parameters ( G f, B ) on structural performance of ETS strengthened beams are examined. Finite element (FE) simulations of ETS strengthened beams considering bond model are evaluated.